Actuator saturation control of a benchmark structure using hedge-algebras-based fuzzy controller - Le, Bui Hai (Vietnam Journal of Mechanics, 2015)
In this paper, the problem of actuator saturation control of a benchmark structure using hedge-algebras-based fuzzy controller (HAC) is presented. In HAC, linguistic values of linguistic terms are obtained through semantically quantifying mappings (SQMs) based on few fuzziness parameters of each linguistic variable without using any fuzzy set and inherent order relationships between linguistic values of each linguistic variable are always ensured. Hence, the design of a HAC leads to determining parameters of SQMs, which are fuzziness measures of primary terms and linguistic hedges occurring in a fuzzy model. As a case study, a HAC is designed to actuator saturation control of a benchmark structure with active bracing system (ABS) subjected to earthquake excitation. Control performance of the controller is also discussed in order to show advantages of the proposed method.